Job satisfaction in doctors with suicidal ideation: a national longitudinal panel study 2002–2021 - Elin Anita Fadum; Øivind Ekeberg; Erlend Hem (BMC Psychiatry)
Abstract Background This study examined the relationship between doctors’ job satisfaction over time and suicidal ideation, additionally describing job satisfaction in doctors who reported suicidal planning and attempt(s). Methods A national panel of Norwegian doctors was surveyed between 2002 and 2021 using Warr’s Job Satisfaction Scale (JSS) in 2002–2021, Maslach Burnout Inventory (MBI) in 2019/2021 and Paykel’s questionnaire for suicidal ideation in 2021. We included 1470 participating doctors in 2021 using multivariate logistic regression models to assess JSS and dimensions of MBI on suicidal ideation. Results Doctors with suicidal ideation (16%) scored on average 4.5 points lower on JSS (95% confidence interval (CI) -6.1 to -2.9) in 2019 with 7.2 points higher values of emotional exhaustion than the reference group (95% CI 5.4 to 9.1). Doctors with suicidal ideation consistently reported less job satisfaction in the period 2002–2021. In multivariate models, less JSS, higher values of emotional exhaustion and lower values of personal accomplishment remained predictors for suicidal ideation, whereas being in a relationship was a protective factor. Lifetime prevalence of suicidal planning and attempt(s) were 8.2% and 1.2%, respectively. Doctors with such suicidal behaviour had the highest values of emotional exhaustion in 2021 (32.1, 95% CI 29.5 to 34.8), but few stated work-problems as the main reason for a suicide attempt. Conclusions Doctors with suicidal ideation had less job satisfaction over a 20-year period prior to their suicidal ideation reports. Doctors with suicidal behaviour had the highest values of emotional exhaustion, but work problems were rarely reported as the main reason for a suicide attempt.